2017
DOI: 10.1002/maco.201709815
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of pure titanium localized corrosion resistance by anodic oxidation

Abstract: The corrosion behavior of commercially pure titanium (UNS R50400) was investigated in presence of aggressive, bromides containing, species; reported to cause severer localized corrosion compared to chlorides. To enhance localized corrosion resistance of the metal, several surface treatments were performed. Samples anodized at potentials between 10 V and 200 V were characterized in term of oxide thickness and morphology and tested with potentiodynamic analyses in NH 4 Br. This treatment was found to greatly enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
4
16
0
Order By: Relevance
“…As the duration of each test did not exceed 8h, no sealing was necessary. Previous works on titanium oxide tested in such conditions showed that nor chemical (ΔpH ≈ 0.05) nor physical (ΔT ≈ 2 °C) deviations were to be expected . In order to ensure repeatability, a minimum of three measurements were made for each treatment procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the duration of each test did not exceed 8h, no sealing was necessary. Previous works on titanium oxide tested in such conditions showed that nor chemical (ΔpH ≈ 0.05) nor physical (ΔT ≈ 2 °C) deviations were to be expected . In order to ensure repeatability, a minimum of three measurements were made for each treatment procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Anodic oxidation produces a compact, adherent, and corrosion resistant oxide and was studied in previous works . However, in case of already installed part, localized treatment, small part or complex geometry, anodic oxidation could be un‐feasible.…”
Section: Introductionmentioning
confidence: 99%
“…The easiest and cheapest treatment to adjust oxide layer is anodic oxidation. It consists in applying an anodic polarization of several tens of volts to the metal, promoting the growth of a compact, adherent and corrosion resistant oxide with thicknesses ranging from about 40 nm with anodizing potential 10 V, to about 250 nm at 100 V. [22][23][24] However, in case of already installed part, localized treatment, small part or complex geometry, anodic oxidation could be un-feasible. In these cases chemical oxidation would be suitable to provide the corrosion resistance enhancement needed.…”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%
“…As the duration of each test did not exceed 8h, no sealing was considered. Previous works on titanium oxide tested in such conditions showed that nor chemical (ΔpH ≈ 0.05) nor physical (ΔT ≈ 2°C) deviations were expected [24]. In order to ensure repeatability, a minimum of three measurements were made for each treatment.…”
Section: Corrosion Testmentioning
confidence: 99%
“…For TiAlV6‐4, there exists a high number of publications on the corrosion behavior in various media, due to the widespread technical use of this alloy. In comparison, less information about the growth mechanism of passivating anodic oxide films are available.…”
Section: Introductionmentioning
confidence: 99%